Typical Platform of a Decision Support System Software Complex in an Enterprise Management System - Hrybkov, Serhii; Litvinov, Valeriy; Oliinyk, Hanna; Chobanu, Valeria (My University, 2020)
Propose model of interoperable aggregate of program platforms that provides performance of all basic stages on creation of a decision-making support subsystem — from construction of a program infrastructure of a subsystem to modular and integration testing of a program code. The proposed software and technology solutions presented in the model have been successfully tested in the decision support system for the formation and operational reconfiguration of production plans for the implementation of enterprise contracts
Keywords: клієнт-сервер; прийняття рішень; веб-орієнтована система; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки